2014
DOI: 10.1002/jez.1869
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of intraspecific variation in carbon and phosphorus kinetics in Daphnia

Abstract: Understanding how the genome interacts with the environment to produce a diversity of phenotypes is a central challenge in biology. However, we know little about how traits involved in nutrient processing interact with key ecological parameters, such as the supply of mineral nutrients, particularly in animals. The framework of ecological stoichiometry uses information on the content of key elements such as carbon (C) and phosphorus (P) in individuals to predict the success of species. Nevertheless, intraspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…It has also been reported that phosphorus supply drives rapid turnover of membrane phospholipids in phytoplankton30. Particularly, in Daphnia it has been shown that under low quality food (i.e., high carbon – C to low phosphorus – P ratio: C:P), this organism can maintain P-homeostasis by reducing C-uptake and/or increasing P-retention, which is in agreement with stoichiometric theory31. Additionally, it has been suggested (and assessed) that the role of organismal C:P ratios may be functionally related to the structural and copy number variation of ribosomal-RNA genes16.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has also been reported that phosphorus supply drives rapid turnover of membrane phospholipids in phytoplankton30. Particularly, in Daphnia it has been shown that under low quality food (i.e., high carbon – C to low phosphorus – P ratio: C:P), this organism can maintain P-homeostasis by reducing C-uptake and/or increasing P-retention, which is in agreement with stoichiometric theory31. Additionally, it has been suggested (and assessed) that the role of organismal C:P ratios may be functionally related to the structural and copy number variation of ribosomal-RNA genes16.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, it has been suggested (and assessed) that the role of organismal C:P ratios may be functionally related to the structural and copy number variation of ribosomal-RNA genes16. Recent studies have reported large differences in gene expression levels under different P-diets in Daphnia at the intra-specific level1731. These previous studies have found hundreds of differentially expressed genes in a comparison between genotypes run under low and high P environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…b). This decrease in retention efficiency in D. pulex under limitation is surprising, considering that previous work has found that, for certain genotypes, P limitation yields an increase in nutrient retention (Roy Chowdhury et al ). However, studies have also found that D. pulex has significantly increased electron transport chain activity compared with D. pulicaria (Simcic and Brancelj ).…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, radiolabeling has been shown to be a reliable indicator of the physiological kinetics of both C and P (e.g. DeMott et al, 1998;He and Wang, 2007;Roy Chowdhury et al, 2014).…”
Section: Discussionmentioning
confidence: 99%